Produção de biomassa de microalgas em meio alternativo de manipueira enriquecido com bicarbonato de sódio - Santos, Guilherme Henrique Porfirio (2019)
Biodiesel production using microalgal biomass can be considered an alternative for the energy sector, since these microorganisms have high productivity and high lipid content. Thus, the objective of this work was to study the development of microalgae Chlorella sp. in alternative medium containing of manipueira enriched whit sodium bicarbonate. Initially a preliminary cultivation was performed to evaluate the development of different strains (BMAK07 and PPEQ – 02) under the mixotrophic and heterotrophic nutrition methods. After comparison, was found the best condition to follow for cultivation, where a DCCR design was carried out with different concentrations of manipueira and different sodium bicarbonate supplements as independent variables. The condition with the best result in the preliminary cultivation was obtained with the strain PPEQ – 02 under the mixotrophic nutrition method and resulted in 643 ± 28.1 mg.L-1 of biomass and 13.43 ± 1.0% of lipids. In cultivation, the best results for the maximum yield of biomass (820 mg.L-1) and lipid content (59%) were achieved in the test twelve (12) with a concentration of 17% (v/v) and supplementation of 15 g.L-1 sodium bicarbonate. The results show that the alternative medium has potential of use for the cultivation of microalgae of the genus.